Advanced nitrogen removal in a single return anaerobic/aerobic/anoxic/aerobic (AnOAO) bioreactor treating municipal wastewater through hydroxylamine addition: Performance and microbial community. (May 2022) - Wang, Jiao; Peng, Yongzhen; Zhang, Qiong; Su, Yunlong; Wang, Shuying; Li, Jianwei
Graphical abstract: Highlights: Achieving NAR (98%) of An OAO reactor by continuously adding NH2 OH in only 2 days. Stable NAR (95%) maintained by decreasing NH2 OH dosing with 1 day every 4 days. TINinf and TINeff were 42.9 and 4.8 mg N/L at aerobic HRT (4.6 h) and DO (<1mg/L) Advanced N-removal by real sewage with low C/N (2.8) without external carbon source. AOB activity increased to 12.78 mg N/(g VSS∙h) while NOB decreased by 81% Abstract: The NH2 OH dosing strategy for nitrogen removal was investigated in a single return continuous-flow anaerobic/aerobic/anoxic/aerobic (An OAO) reactor fed with real municipal wastewater. A high nitrite accumulation ratio of 98% was achieved in only two days by continuously adding 10 mg/L NH2 OH. When gradually reducing dosing frequency to one day every four days, effluent total nitrogen was as low as 4.8 ± 2.2 mg N/L with removal efficiency of 88.7 ± 5.3%, under aerobic HRT of 4.6 h, DO below 1.0 mg/L, and C/N of 2.8 without external carbon sources. Batch test showed that nitrite oxidizing bacteria (NOB) activity decreased by 81% after adding NH2 OH, while ammonia oxidizing bacteria (AOB) activity remained stable. qPCR confirmed that NOB abundance decreased, and 16S rRNA sequencing further showed that g_ Nitrospira belonging to NOB decreased significantly (P < 0.001). Overall, this study provides a novel strategy for advanced nitrogen removal from municipal wastewater in continuous flow systems.